2020
DOI: 10.1111/jocs.14412
|View full text |Cite
|
Sign up to set email alerts
|

Minimally‐invasive parasternal aortic valve replacement–A slow learning curve towards improved outcomes

Abstract: Background We report our starting experience with parasternal minimally‐invasive aortic valve replacement. Methods From 7/14 to 8/18, 192 received classic aortic valve surgery using a 5 cm parasternal incision and percutaneous groin cannulation. Patients were selected based on anatomic feasibility judged by preoperative computed tomography‐scan. Except for porcelain aorta, left‐sided aortic location, or endocarditic abscess, there were no exclusions. Results Patients were divided into two groups (first and sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Various studies have shown that RAMT AVR is associated with a low rate of postoperative complications and favorable midterm survival 19,23,24,36–46 . Our center established a minimally invasive surgical program dedicated to the sternum‐sparing RAMT approach in 2016.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have shown that RAMT AVR is associated with a low rate of postoperative complications and favorable midterm survival 19,23,24,36–46 . Our center established a minimally invasive surgical program dedicated to the sternum‐sparing RAMT approach in 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Operative setup for the right anterior minithoracotomy (RAMT) approach. (B) Exposure of the aortic valve through a RAMT Various studies have shown that RAMT AVR is associated with a low rate of postoperative complications and favorable midterm survival 19,23,24,[36][37][38][39][40][41][42][43][44][45][46]. Our center established a minimally invasive…”
mentioning
confidence: 99%
“…5C, D ). 34 47 48 Thus, individual decision-making, taking local expertise, and prognosis for the individual patient into account seem to be the most promising way for optimal patient care.…”
Section: Surgical Treatment Of Valve Diseasementioning
confidence: 99%
“…We presented our experience of the first almost 200 patients with parasternal minithoracotomy for aortic valve replacement. 52 We used conventional prostheses with classic suturing and tying (clamp times 78 þ 24 minutes). We demonstrated in this Fig.…”
Section: Classic Aortic Valve Surgerymentioning
confidence: 99%
“…(B) Comparison of the treatment effect of early surgical aortic valve replacement compared with conservative management in relation to the degree of chronic kidney disease 47 (reproduced with permission). (C) Photograph (left) of the surgical access and the ratio of observed to expected mortality (right panel, first and second half of experience) in a complete series of patients having undergone parasternal aortic valve replacement at a single institution 52 (reproduced with permission). 20,000 patients from 14 studies, the authors report a survival advantage for mechanical valves in a propensity-matched comparison.…”
Section: Mitral and Tricuspid Valve Surgery Mitral Valvementioning
confidence: 99%